Manufatura enxuta: estrutura para implementação em empresas de produção não seriada do tipo “Engineer-to- Order”, ETO - Tamberg, Edgar Tivelli (2019)
Lean manufacturing is a paradigm increasingly adopted in the serial product industry, which can be observed both in the literature and in company practice. However, for engineer-to-order (ETO) industries, both academic production and practical use by such industries are very limited. For this reason, this study makes a research about the application of the system of lean manufacturing in companies of non-serial, engineer-to-order (ETO) type. Through a review of the existing literature, we verified the models of implementation processes or frameworks and tools used to enable the adoption of lean manufacturing in companies of type ETO and from this evaluation a specific model was proposed for industries of goods under order not serial. The validation of the proposed framework was done through an action research conducted in a company that manufactures custom capital goods, specifically large electromechanical equipment. This type of industry most often produces only one piece at a time, and thus a representative piece was chosen within the set of products that form an electrical generating unit and that was part of the critical path of the product. From this pilot project, the pertinent techniques and tools were implemented according to the proposed framework so that the sequence of activities, the way of working and the results obtained in the production validated the proposal of application of lean manufacturing in this type of production, as well as evidence of significant gains from this type of implementation.